Administration of sodium-glucose cotransporter-2 inhibitors in kidney transplant patients with diabetes: a systematic review and meta-analysis - Hamidreza Khodabandeh; Zahra Bakhshizade; Mohammad Hossein Taklif; Halime Zaeri Fakhrabadi; Soleyman Alivand; Noorbakhsh Alivand; Ghazaleh Rashidizadeh; Leila Jampour; Mahsa Shirani (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Sodium-glucose cotransporter-2 (SGLT2) inhibitors are a new diabetes treatment. Considering the prescription of these medicines for kidney transplant patients, this systematic review and meta-analysis aimed to investigate the impact of SGLT2 inhibitors on kidney transplant patients. Material and Methods: This meta-analysis study was performed based on the PRISMA guideline. The necessary data were collected by searching the databases of Scopus, PubMed, Cochrane, Google Scholar search engine, and Web of Science without a time limit until March 1, 2023. The data were analyzed in STATA 14. A P value less than 0.05 was considered significant. Results: The authors assessed eight articles with a sample size of 960 patients. The SGLT2 inhibitors showed no significant impact on levels of estimated glomerular filtration rate [SMD: -0.21 (95% CI: -0.65, 0.25)], serum creatinine [SMD: -0.02 (95% CI: -0.19, 0.15)], plasma hemoglobin A1c (HbA1c) [SMD: -0.62 (95% CI: -1.43, 0.18)], systolic blood pressure [SMD: -0.64 (95% CI: -1.80, 0.52)], and diastolic blood pressure [SMD: -0.64 (95% CI: -1.41, 0.14)], and on the patient's weight [SMD:-0.31 (95% CI: -0.80, 0.18)]. Patient age did not influence the impact of SGLT2 inhibitors on estimated glomerular filtration rate (50-59 years-old age group: [SMD: 0.13 (95% CI: -0.04, 0.30)], 60-69 years-old age group: [SMD: -0.56 (95 % CI: -1.38, 0.26]). Duration of medicine use did not affect the impact of SGLT2 inhibitors on estimated glomerular filtration rate [6 months after medicine use: SMD: -0.56 (95% CI: -1.38, 0.26)], 12 months after medicine use: [SMD: 0.10 (95% CI: -0.05, 0.26)]. Conclusion: SGLT2 inhibitors were not effective in lowering blood pressure, estimated glomerular filtration rate, serum creatinine, and hemoglobin A1c levels, or weight in kidney transplant patients. Although SGLT2 inhibitors were ineffective in improving kidney transplant patients' renal function, there were no side effects, and the administration of this drug in kidney transplant patients can continue. Further research is required to ensure safety and determine the appropriate dosage and duration of drug use. Registration: The study was compiled according to the PRISMA checklist and its protocol was registered on the PROSPERO (ID: CRD42023407501) and Research Registry (UIN: reviewregistry1666) websites.